Weaving the Imperial Breadbasket: Nationalism, Empire and the Triumph of Canadian Wheat, 1890-1940 - Tošaj, Nicholas (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2017)
Canadian wheat has occupied a prominent place in the global market since the late 19th century. Ideal for bread-baking, the high-protein wheat grown on the Canadian prairies was a highly valued export. The efforts undertaken to adapt wheat to Canadian agriculture, and the subsequent success of Canada’s wheat export market, contributed to building Canadian nationhood both at home and abroad. The prominence of Canadian wheat is a testament to the success of imperial agricultural developments and the connections woven by empires. Britain’s creation of an agricultural hinterland within Canada through the expansion of its empire’s food supply defined how a new nation emerged through an old-world dependency on wheat. The wheat produced by Canadian farmers flowed into both the British and French empires, filling crucial roles throughout each of these imperial structures. Divergent reactions to these imports speak to wheat’s importance both as a staple foodstuff and a bearer of cultural significance.